1993
DOI: 10.1002/j.1460-2075.1993.tb05651.x
|View full text |Cite
|
Sign up to set email alerts
|

The SecA and SecY subunits of translocase are the nearest neighbors of a translocating preprotein, shielding it from phospholipids.

Abstract: To study the environment of a preprotein as it crosses the plasma membrane of Escherichia coli, unique cysteinyl residues were introduced into proOmpA and the genes for these mutant preproteins were fused to the gene of dihydrofolate reductase (Dhfr). A photoactivable, radiolabeled and reducible cross‐linker was then attached to the unique cysteinyl residue of each purified protein. Partially translocated polypeptides were generated and arrested in their membrane transit by the folded structure of the dihydrof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
132
0
7

Year Published

1993
1993
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 74 publications
7
132
0
7
Order By: Relevance
“…The process of intraorganellar protein transport from the stroma into the thylakoids may thus resemble that of intracellular protein transport in ancestral cyanobacteria, whereas the process of protein transport from the cytosol into the stroma may represent that acquired after the endosymbiotic event . It was shown that translocation of a dihydrofolate reductase fusion protein across the Escherichia coli cytoplasmic membrane was blocked by methotrexate and NADPH (Joly and Wickner, 1993). This may be consistent from an evolutionary point of view with our findings that the thylakoids do not have the capacity to take up the methotrexate-bound, tightly folded dihydrofolate reductase fusion protein.…”
Section: Discussionsupporting
confidence: 92%
“…The process of intraorganellar protein transport from the stroma into the thylakoids may thus resemble that of intracellular protein transport in ancestral cyanobacteria, whereas the process of protein transport from the cytosol into the stroma may represent that acquired after the endosymbiotic event . It was shown that translocation of a dihydrofolate reductase fusion protein across the Escherichia coli cytoplasmic membrane was blocked by methotrexate and NADPH (Joly and Wickner, 1993). This may be consistent from an evolutionary point of view with our findings that the thylakoids do not have the capacity to take up the methotrexate-bound, tightly folded dihydrofolate reductase fusion protein.…”
Section: Discussionsupporting
confidence: 92%
“…Due to its location at the core of the transport machinery, it has been the focus of considerable research aimed at understanding its structure and function. Previous studies have shown that E. coli SecY comes into close contact with the translocating polypeptide chain (33) and, in yeast, the signal peptide forms a helix in the process (34). We have now shown that the interaction is saturable and specific for functional signal peptides; neither a nonfunctional signal peptide nor an unrelated peptide effectively competes for binding.…”
Section: Discussionmentioning
confidence: 67%
“…1,2 In bacteria, a central role in both processes is fulfilled by the integral membrane complex SecYEG, that forms the protein conducting channel within the cytoplasmic membrane. 3,4 Two different cytoplasmic partners can bind to SecYEG to induce opening of the channel and to provide the driving force for the translocation process. Membrane proteins are mostly inserted cotranslationally by SecYEG-bound ribosomes whereas secretory proteins and large extracellular domains of integral membrane proteins are translocated posttranslationally by the motor protein SecA.…”
Section: Introductionmentioning
confidence: 99%